2012
DOI: 10.1080/10934529.2012.672140
|View full text |Cite
|
Sign up to set email alerts
|

Structural and ultrastructural study of the rabbit testes exposed to carbamate insecticide

Abstract: The present study was conducted to investigate the impact of carbamate insecticide - bendiocarb on the testicular structure of adult rabbits. Bendiocarb was perorally administered daily for 10 and 30 days, at a dose 5 mg/kg of body weight. After the histological sampling the tissues were investigated and compared with control. After the bendiocarb administration the absolute and relative testicular weight decreased significantly (P < 0.001) in both time periods. The testicular parenchyma showed structural chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Carbamate also induced changes in rabbit testes. Almasiova et al [8] observed sloughing of developing sex cells in testicular parenchyma and vacuoles within Sertoli cells. The intestinal Leydig cells were smaller with shrivelled nuclei and strongly vacuolar dark cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Carbamate also induced changes in rabbit testes. Almasiova et al [8] observed sloughing of developing sex cells in testicular parenchyma and vacuoles within Sertoli cells. The intestinal Leydig cells were smaller with shrivelled nuclei and strongly vacuolar dark cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of bendiocarb poisoning include weakness, blurred vision, headache, nausea, abdominal cramps, chest discomfort, miosis, sweating, muscle tremors and incoordination, decreased pulse, low blood pressure, heart irregularities, giddiness, confusion, slurred speech, and loss of reflexes. Respiratory failure resulting from inhibition of the central respiratory drive and bronchospasms coupled with depolarizing blockade at neuromuscular junctions‐diaphragm and intercostals (Krieger, ; Almasiova et al, ). Many studies proved that bendiocarb increases incidence of lymphoreticular tumours, such as lymphosarcomas, reticulosarcomas, lymphoid, and myeloid leukaemia (Dorko et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Neurotoxicity as the main impact of carbamates as well as alterations of homeostasis (Sobekova et al 2009;Capcarova et al 2010;Mojzisova et al 2012) or other important organs such as thymus (Flesarova et al 2007), lymphoid tissue , liver (Holovska et al 2011;Pollakova et al 2012), spleen (Petrovova et al 2011), and testes (Almasiova et al 2012) have been studied in great detail.…”
Section: Discussionmentioning
confidence: 99%